Microgel modified asphalt and preparation method thereof
By using gamma-ray crosslinked styrene butadiene microgel modified asphalt, the problem of insufficient storage stability of SBS modified asphalt at high temperatures is solved, higher storage stability and service life are achieved, and interface adhesion is improved.
Patent Information
- Application Number
- CN202510030225.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
The existing SBS modified asphalt has insufficient storage stability at high temperatures, which is prone to macroscopic phase separation, and low thermal conductivity leads to long heating time and inconvenient use.
Using intramolecular crosslinking polymer micro network structure, irradiated crosslinking of styrene butadiene latex through γ rays, a styrene butadiene microgel is prepared and mixed with petroleum asphalt to form microgel modified asphalt.
The storage stability of modified asphalt at viscous fluid temperature is improved, the viscosity is reduced, the service life is extended, and the interface adhesiveness with aggregate is enhanced.
Smart Images

Figure BDA0005233930480000041 
Figure BDA0005233930480000071 
Figure HDA0005233930490000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of asphalt, and more specifically, to a microgel-modified asphalt and a preparation method thereof. Background Art
[0002] Asphalt is a mixture of various complex organic molecules with an average molecular weight of about 1000g / mol. According to solubility, it can be divided into four components: fat, aromatic, resin and asphaltene. Due to the low average molecular weight of asphalt, the performance of asphalt is greatly affected by temperature, and there are problems such as low strength and greater brittleness in low temperature environments. In order to meet the increased performance requirements of high-grade highways, polymers are often used to modify asphalt. Many polymers can be used to modify asphalt, but SBS (styrene-butadiene-styrene block copolymer) is currently the most used polymer in modified asphalt because of its good dispersibility in asphalt, as well as the excellent performance and acceptable cost of the modified asphalt. The use and research of SBS modified asphalt began in the 1970s. In China's highway construction, the use of SBS modified asphalt accounts for more than 90%.
[0003] The existing SBS modified asphalt is non-flowing at room temperature and needs to be heated to a flowable state before use. However, due to the low thermal conductivity of SBS modified asphalt and the large amount of SBS modified asphalt used in engineering, it takes a long time to heat a large amount of SBS modified asphalt from room temperature to a flowable state, which is extremely inconvenient. Therefore, from the perspective of ease of use, SBS modified asphalt is usually stored at a higher viscous flow temperature, such as above 100°C. However, when SBS modified asphalt is stored at high temperature for a long time, macroscopic phase separation often occurs. The principle is mainly: the PB segment in the SBS molecule, which is in a rubbery state at room temperature, has a stretched conformation in the asphalt due to its good compatibility with the fat and aromatic components in the asphalt; while the polystyrene (PS) segment, which is not compatible with asphalt, phase separates into a PS-rich phase, which is in a glassy state at room temperature and is maintained as a physical crosslinking point in the SBS network structure that is significantly swollen in the asphalt. The glass transition temperature (Tg) of PS is less than 100°C. When SBS modified asphalt is stored above 100°C, since the storage temperature is higher than the Tg of PS, the PS segments can slip, and the PS-enriched micro-regions are gradually destroyed under the action of the elastic recovery force of the PB segments, causing the SBS network structure that is significantly swollen in the asphalt to collapse, thereby causing the SBS molecules to macroscopically separate from the asphalt under the drive of the movement of the PS segments.
[0004] One way to solve the problem of insufficient high-temperature storage stability of SBS modified asphalt is to add an interfacial compatibilizer, such as sulfur that can react with aromatic components in asphalt and SBS containing double bonds, to the SBS modified asphalt that has been swollen and evenly dispersed in the asphalt. However, the strong odor of hydrogen sulfide produced by the dehydrogenation reaction of sulfur and asphalt significantly increases environmental pollution, and sulfur-modified SBS modified asphalt is more easily oxidized. There are also problems such as difficulty in recycling and poor storage stability of polysulfide bonds. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a microgel modified asphalt and a preparation method thereof, aiming to modify the asphalt by replacing the SBS macroscopic network structure in the SBS modified asphalt with an intramolecular cross-linked polymer microscopic network structure, thereby increasing the storage stability and other properties of the modified asphalt at viscous flow temperature.
[0006] The asphalt of the present application can be petroleum asphalt made in various ways, such as asphalt made by distillation, i.e. straight-run asphalt, asphalt made by solvent precipitation, asphalt made by oxidation, i.e. oxidized asphalt, asphalt made by blending, and asphalt made by emulsification, i.e. emulsified asphalt.
[0007] In the first aspect, the present application provides a microgel modified asphalt, which adopts the following technical solution: A microgel modified asphalt comprises styrene butadiene microgel and asphalt, wherein the amount of the styrene butadiene microgel is 4-6wt% of the amount of the asphalt.
[0008] Preferably, the amount of the styrene-butadiene microgel used is 5wt% of the amount of asphalt used.
[0009] Preferably, the styrene butadiene microgel is prepared by cross-linking styrene butadiene latex by gamma irradiation, and the average molecular weight between the cross-linking points is 2500-22500 g / mol.
[0010] Through the above technical scheme, the present application uses gamma rays to irradiate and crosslink styrene butadiene latex, so that the C=C double bonds in the polybutadiene chain segments of the styrene butadiene molecules in the styrene butadiene latex are lightly crosslinked, and a styrene butadiene microgel with a chemically crosslinked network structure is obtained, which is then mixed with petroleum asphalt, which can not only play a similar modification effect on petroleum asphalt as the physically crosslinked SBS polymer network structure, but also improve the various performance indicators of petroleum asphalt, but also can be stably stored at high temperatures, reducing the possibility of polymer macrophase separation during storage due to insufficient temperature stability of the modified petroleum asphalt, and improving the stability of the modified petroleum asphalt at viscous flow temperature. Moreover, when the addition amount or modification effect is equivalent, compared with SBS modified petroleum asphalt, the styrene butadiene microgel modified petroleum asphalt of the present application has a lower viscosity, reduces the aging degree caused by the need for a higher melting temperature of the modified petroleum asphalt when in use, and prolongs the service life of the modified petroleum asphalt. In addition, the styrene butadiene microgel of the present application can also increase the interface adhesion between the modified petroleum asphalt and the new and old aggregates, and improve the performance of the modified asphalt.
[0011] At the same time, the present application controls the crosslinking degree of styrene butadiene latex during irradiation crosslinking, so that it is only slightly crosslinked, and can swell better in petroleum asphalt, so that it can absorb more fat and aromatic components that have good compatibility with polybutadiene segments but low softening points from petroleum asphalt. Compared with SBS, the styrene butadiene microgel of the present application can further improve the softening point and other properties of modified petroleum asphalt. However, if the crosslinking degree is large, or after complete crosslinking, the styrene butadiene microgel will not be effectively swelled in petroleum asphalt, and thus cannot have a good modification effect on petroleum asphalt.
[0012] Preferably, the average molecular weight between the cross-linking points of the styrene-butadiene microgel is 10,000-17,000 g / mol.
[0013] Preferably, the average molecular weight between crosslinking points of the styrene-butadiene microgel is 15000 g / mol.
[0014] Through the above technical solution, the present application further optimizes the crosslinking degree of styrene butadiene microgel, thereby further improving the modification effect of styrene butadiene microgel on petroleum asphalt. The test results show that when the average molecular weight between the crosslinking points of styrene butadiene microgel is 15000g / mol, the modification effect of styrene butadiene microgel on petroleum asphalt is better.
[0015] Preferably, the polybutadiene content in the styrene-butadiene microgel is ≥10wt%.
[0016] By adopting the above technical solution, the styrene-butadiene microgel can adsorb more components in petroleum asphalt such as fat and aromatic components with lower softening points and similar polarity to polybutadiene, thereby improving the modification effect of the styrene-butadiene microgel on petroleum asphalt.
[0017] Preferably, the polybutadiene content in the styrene-butadiene microgel is ≥50wt%.
[0018] By adopting the above technical scheme, the present application further optimizes the polybutadiene content in the styrene-butadiene microgel, which can further improve the modification effect of the styrene-butadiene microgel on petroleum asphalt, thereby further improving various performance indicators of the modified petroleum asphalt.
[0019] In the second aspect, the present application provides a method for preparing microgel modified asphalt, which adopts the following technical scheme: A method for preparing microgel modified asphalt comprises the following steps: S1, preparing styrene butadiene microgel, mixing styrene butadiene latex and a radiation sensitizer at room temperature, stirring evenly, and then sealing and standing and irradiating the mixture with gamma rays to obtain styrene butadiene microgel; S2, preparing microgel modified asphalt, mixing the styrene butadiene microgel prepared in step S1 and asphalt at a rotation speed of 800-1200 rpm for 5-8 minutes to obtain microgel modified asphalt.
[0020] In summary, this application has the following beneficial technical effects: 1. The modified petroleum asphalt of the present application not only has higher performance than SBS modified petroleum asphalt, but also can be stably stored at high temperatures, reducing the possibility of polymer macrophase separation during storage due to insufficient temperature stability of the modified petroleum asphalt, and improving the stability of the modified petroleum asphalt at viscous flow temperature; 2. When the addition amount or modification effect is equivalent, compared with SBS modified petroleum asphalt, the styrene-butadiene microgel modified petroleum asphalt of the present application has a lower viscosity, reduces the aging degree caused by the higher melting temperature required for the modified petroleum asphalt during use, and extends the service life of the modified petroleum asphalt; 3. The modified petroleum asphalt obtained in this application has high interfacial adhesion with new and old aggregates, which improves the stability and durability of the modified asphalt pavement, enhances the bearing capacity of the pavement, reduces pavement damage and maintenance costs, and improves driving safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structure of using the styrene-butadiene microgel of the present application to replace SBS modified asphalt. DETAILED DESCRIPTION
[0022] The following examples further illustrate the present application in detail.
[0023] Unless otherwise specified, the raw materials used in this application are all commercially available products.
[0024] The asphalt of the present application can be petroleum asphalt made in various ways, such as asphalt made by distillation, i.e. straight-run asphalt, asphalt made by solvent precipitation, asphalt made by oxidation, i.e. oxidized asphalt, asphalt made by blending, and asphalt made by emulsification, i.e. emulsified asphalt.
[0025] In the specific implementation of the present application, three commercially available types of emulsified asphalt are used as examples for illustration. The components and indicators of these three types of emulsified asphalt are shown in Table 1 and Table 2, respectively.
[0026] Table 1 Asphalt composition Element Dashan 90# Donghai 70# SK90# Saturation (%) 7.6603 5.7713 6.0795 Aroma content (%) 45.1593 56.0916 39.0993 Gel(%) 11.6832 10.7681 12.3986 Asphaltene (%) 35.4971 27.3690 42.4226 Colloid instability index 0.7592 0.4957 0.9418 Table 2 Asphalt index table index Dashan 90# Donghai 70# SK90# Softening point(℃) 47.6 48.2 45.0 Needle penetration (0.1mm) 75.1 61.4 93.0 15℃ Elongation(cm) >100 >100 >100 Frass brittle point (℃) -10 -4 -9 The styrene butadiene latex of the present application is a carboxyl-terminated styrene butadiene latex, which can be prepared by oneself or purchased from the market. In the specific implementation manner of the present application, the following three commercially available styrene butadiene latexes are used as examples for illustration, and the specific parameters are shown in Table 3.
[0027] Table 3 Basic parameters of styrene-butadiene latex The radiation sensitizer of the present application is a radiation sensitizer commonly used in the art. In the specific implementation of the present application, 2-ethylhexyl acrylate (2-EHA) is used as an example for illustration.
[0028] The radiation source used for the radiation cross-linking of the present application is a cobalt-60 radiation source.
[0029] The average molecular weight between the crosslinking points of the styrene-butadiene microgel of the present application is adjusted by the irradiation dose and the amount of the irradiation sensitizer, that is, those skilled in the art can obtain the average molecular weight between the crosslinking points required by the present application by adjusting the irradiation dose and the amount of the irradiation sensitizer.
[0030] Example 1.1 A method for preparing microgel modified asphalt comprises the following steps: S1, prepare styrene butadiene microgel, 0.4kg of 1# styrene butadiene latex and 0.004kg of 2-ethylhexyl acrylate (2-EHA) are mixed and stirred at room temperature, then sealed and allowed to stand and irradiated at room temperature using a cobalt-60 radiation source, when the irradiation dose reaches 1.5kGy / h, the reactor is turned upside down and irradiated again, when the irradiation dose reaches 3kGy / h, the irradiation is stopped to obtain styrene butadiene microgel; after testing, the cross-linking point average molecular weight of the styrene butadiene microgel is 15000g / mol; S2. Prepare microgel modified asphalt. Mix 0.4 kg of the styrene butadiene microgel prepared in step S1 and 10 kg of petroleum emulsified asphalt (Donghai 70#) at a rotation speed of 800 rpm for 8 min to obtain microgel modified asphalt.
[0031] Example 1.2 A method for preparing microgel modified asphalt comprises the following steps: S1, prepare styrene butadiene microgel, 0.4kg of 1# styrene butadiene latex and 0.004kg of 2-ethylhexyl acrylate (2-EHA) are mixed and stirred at room temperature, then sealed and allowed to stand and irradiated at room temperature using a cobalt-60 radiation source, when the irradiation dose reaches 1.5kGy / h, the reactor is turned upside down and irradiated again, when the irradiation dose reaches 3kGy / h, the irradiation is stopped to obtain styrene butadiene microgel; after testing, the cross-linking point average molecular weight of the styrene butadiene microgel is 15000g / mol; S2. Prepare microgel modified asphalt. Mix 0.6 kg of the styrene butadiene microgel prepared in step S1 and 10 kg of petroleum emulsified asphalt (Donghai 70#) at a rotation speed of 1200 rpm for 5 min to obtain microgel modified asphalt.
[0032] Example 1.3 A method for preparing microgel modified asphalt comprises the following steps: S1, prepare styrene butadiene microgel, 0.4kg of 1# styrene butadiene latex and 0.004kg of 2-ethylhexyl acrylate (2-EHA) are mixed and stirred at room temperature, then sealed and allowed to stand and irradiated at room temperature using a cobalt-60 radiation source, when the irradiation dose reaches 1.5kGy / h, the reactor is turned upside down and irradiated again, and when the irradiation dose reaches 3kGy / h, the irradiation is stopped to obtain styrene butadiene microgel; after testing, the average molecular weight between crosslinking points of the styrene butadiene microgel is 15000g / mol; S2. Prepare microgel modified asphalt. Mix 0.5 kg of the styrene butadiene microgel prepared in step S1 and 10 kg of petroleum emulsified asphalt (Donghai 70#) at a rotation speed of 1000 rpm for 6 min to obtain microgel modified asphalt.
[0033] Example 1.4 A method for preparing microgel modified asphalt, which is different from Example 1.3 in that: Donghai 70# petroleum emulsified asphalt in step S2 is replaced by Dashan 90# petroleum emulsified asphalt, and the rest is the same as Example 1.3.
[0034] Example 1.5 A method for preparing microgel modified asphalt, which is different from Example 1.3 in that: Donghai 70# petroleum emulsified asphalt in step S2 is replaced by SK90# petroleum emulsified asphalt, and the rest is the same as Example 1.3.
[0035] Example 2.1 A method for preparing microgel-modified asphalt is different from that of Example 1.3 in that the average molecular weight between the crosslinking points of the styrene-butadiene microgel prepared in step S1 is 2500 g / mol, and the rest is the same as that of Example 1.3.
[0036] Example 2.2 A method for preparing microgel-modified asphalt is different from that of Example 1.3 in that the average molecular weight between the crosslinking points of the styrene-butadiene microgel prepared in step S1 is 10,000 g / mol, and the rest is the same as that of Example 1.3.
[0037] Example 2.3 A method for preparing microgel-modified asphalt is different from that of Example 1.3 in that the average molecular weight between the crosslinking points of the styrene-butadiene microgel prepared in step S1 is 17000 g / mol, and the rest is the same as that of Example 1.3.
[0038] Example 2.4 A method for preparing microgel-modified asphalt is different from that of Example 1.3 in that the average molecular weight between the crosslinking points of the styrene-butadiene microgel prepared in step S1 is 22500 g / mol, and the rest is the same as that of Example 1.3.
[0039] Example 3.1 A method for preparing microgel modified asphalt, which is different from Example 1.3 in that: 1# styrene butadiene latex in step S1 is replaced by 2# styrene butadiene latex, and the rest is the same as Example 1.3.
[0040] Example 3.2 A method for preparing microgel modified asphalt, which is different from Example 1.3 in that: 1# styrene butadiene latex in step S1 is replaced by 3# styrene butadiene latex, and the rest is the same as Example 1.3.
[0041] Comparative Example 1 The difference from Example 1.3 is that the average molecular weight between the cross-linking points of the styrene-butadiene microgel prepared in step S1 is 1000 g / mol, and the rest is the same as Example 1.3.
[0042] Comparative Example 2 The difference from Example 1.3 is that the styrene-butadiene microgel in step S2 is replaced by SBS rubber latex, and the rest is the same as Example 1.3. The SBS rubber latex has an effective ingredient content of 51%, an initial decomposition temperature between 220-240°C, and a pH value of 4.0-5.0.
[0043] Comparative Example 3 The difference from Example 1.3 is that the styrene butadiene microgel in step S2 is replaced by 1# styrene butadiene latex, and the rest is the same as Example 1.3.
[0044] Performance Testing 1. Referring to JTJT20-2011 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", the modified petroleum asphalt prepared in the above examples and comparative examples was tested for relevant properties, and the results are shown in Table 4.
[0045] Table 4 Performance test results As can be seen from Table 4, the softening point of the modified petroleum asphalt obtained in Examples 1.1-1.3 of the present application is 65.8-66.3, the needle penetration (0.1mm) is 49.7-55.6, the ductility at 15°C is >100cm, and the Fras brittle point is -10°C. All properties are better than the unmodified Donghai 70# emulsified asphalt, and the various properties of the modified petroleum asphalt obtained in Example 1.4 are also better than the unmodified Dashan 90# petroleum asphalt, and the various properties of the modified petroleum asphalt obtained in Example 1.5 are also better than the unmodified SK90# petroleum asphalt. It can be seen that the styrene-butadiene microgel of the present application can have a good modification effect on petroleum asphalt and effectively improve the various properties of petroleum asphalt. Among them, by comparing the data between Examples 1.1-1.3, it can be found that when Example 1.3 further optimizes the addition amount of styrene-butadiene microgel, the various properties of the modified petroleum asphalt can be further improved.
[0046] The difference between Examples 2.1-2.4 and Example 1.3 is that the crosslinking degree of the styrene butadiene microgel prepared in step S1 is different. It can be seen from Table 4 that when the average molecular weight between the crosslinking points of the styrene butadiene microgel is too small or too large (Example 2.1, Example 2.4), that is, the crosslinking degree is too small or too large, the modification effect of the styrene butadiene microgel on petroleum asphalt will be reduced. This is mainly because the crosslinking degree is too small or too large. It will affect the swelling effect of the styrene butadiene microgel in petroleum asphalt, thereby affecting the modification effect. By comparing the data between Examples 2.1-2.4 and Example 1.3, it can be found that when Examples 2.2-2.3 further optimize the average molecular weight between the crosslinking points of the styrene butadiene microgel to 10000-17000g / mol, the modification effect of the styrene butadiene microgel on petroleum asphalt can be further improved. When Example 1.3 further controls the average molecular weight between the crosslinking points of the styrene butadiene microgel to 15000g / mol, the modification effect of the styrene butadiene microgel on petroleum asphalt is better.
[0047] The difference between Examples 3.1-3.2 and Example 1.3 is that butadiene styrene microgels with different polybutadiene contents are used. As can be seen from Table 4, the various properties of the modified petroleum asphalt prepared in Examples 3.1-3.2 are lower than those in Example 1.3. It can be seen that the content of polybutadiene in the butadiene styrene microgel has a significant effect on the effect of the butadiene styrene microgel on the modification of the petroleum asphalt. When Example 1.3 further optimizes the content of polybutadiene in the butadiene styrene microgel, the modification effect of the butadiene styrene microgel on the petroleum asphalt can be further improved.
[0048] The difference between Comparative Example 1 and Example 1.3 is that a styrene-butadiene microgel with a very high degree of crosslinking is used. As can be seen from Table 4, the various properties of the modified petroleum asphalt prepared in Comparative Example 1 are almost the same as those of the unmodified petroleum asphalt. It can be seen that when the crosslinking degree of the styrene-butadiene microgel is too high, the styrene-butadiene microgel cannot swell in the petroleum asphalt, and thus cannot have a good modification effect on the petroleum asphalt.
[0049] The difference between Comparative Example 2 and Example 1.3 is that the petroleum asphalt is modified by using SBS rubber latex. As can be seen from Table 4, the various properties of the modified petroleum asphalt prepared in Comparative Example 2 are lower than those in Example 1.3. It can be seen that the present application uses butadiene-styrene microgel to modify the petroleum asphalt, which can not only achieve a modification effect similar to that of SBS, but can even achieve a modification effect better than that of SBS.
[0050] The difference between Comparative Example 3 and Example 1.3 is that the petroleum asphalt is directly modified by using non-irradiated cross-linked styrene butadiene latex. As can be seen from Table 4, the various properties of the modified petroleum asphalt obtained in Comparative Example 3 are lower than those in Example 1.3. It can be seen that the present application first irradiates the styrene butadiene latex to make it slightly cross-linked and then modifies the petroleum asphalt. Compared with directly adding styrene butadiene latex, the various properties of the petroleum asphalt can be further improved.
[0051] 2. In order to compare the viscosity of petroleum asphalt modified by styrene butadiene microgel of the present application with that of petroleum asphalt modified by polymers such as SBS and styrene butadiene latex at different shear rates, the present application further performs viscosity tests on Example 1.3 and Comparative Examples 2-3. The viscosity test is performed on a HR20 dynamic shear rheometer produced by TA Instruments in the United States. The sample is placed on a 2° cone plate with a diameter of 40 mm and a plate spacing of 52 μm. During the test, the sample is first kept at a constant temperature for 15 minutes at a specified temperature, and then the viscosity is tested at an initial shear rate of 1s-1. The test temperatures are 135°C, 150°C and 165°C, respectively. The viscosity test at different shear rates is performed at a temperature of 135°C, and the shear rate increases by 1, 5, 20, 50, 100, and 200 1s. The sample is kept at a constant temperature for 60s before each test. The results are shown in Table 5.
[0052] Table 5 Viscosity test results Unit: Pa·s project 135℃(1s-1) 150℃(1s-1) 165℃(1s-1) 135℃(200s-1) Example 1.3 5.61 2.72 2.57 2.37 Comparative Example 2 4.72 2.35 1.09 4.01 Comparative Example 3 4.84 2.43 1.15 4.13 As can be seen from Table 5, at a lower shear rate, the viscosity of the modified asphalt prepared in Example 1.3 of the present application is higher than that of Comparative Examples 2-3. This is because the degree of swelling of the styrene-butadiene microgel in petroleum asphalt is relatively high, which increases the volume fraction. When the shear rate increases, the viscosity of the modified petroleum asphalt decreases rapidly with the increase in the shear rate. At a higher shear rate, the viscosity of Example 1.3 is significantly lower than that of Comparative Examples 2-3. This is because the interaction between the microscopic network structures in the modified asphalt of the present application is relatively weak, and compared with the macroscopic network structure formed by the swelling of polymers such as SBS rubber emulsion or styrene-butadiene latex in petroleum asphalt, it is easier to be destroyed at a high shear rate, that is, it has a higher thixotropy, is easy to spread and compact during construction, has good construction performance, and has a strong ability to resist deformation by external forces, has a longer service life, and a lower viscosity reduces the degree of aging caused by the higher melting temperature required for the modified petroleum asphalt during use, further extending the service life of the modified petroleum asphalt.
[0053] 3. In order to further compare the high temperature stability of the petroleum asphalt modified by the styrene butadiene microgel of the present application with the petroleum asphalt modified by polymers such as SBS and styrene butadiene latex, the present application further refers to JTJT20-2011 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" to prepare samples of the modified petroleum asphalt obtained in Example 1.3 and Comparative Examples 2-3, and detect the rheological viscosity of the asphalt in the upper and lower parts of the sample tube. The detection temperature is 150°C. The results are shown in Table 6.
[0054] Table 6 High temperature storage stability results Unit: Pa·s project Top tube Down tube Example 1.3 6.01 3.76 Comparative Example 2 18.54 0.92 Comparative Example 3 19.79 0.46 The high-temperature storage stability of the modified petroleum asphalt is characterized by its rheological viscosity. It can be seen from Table 6 that the high-temperature storage stability of the modified petroleum asphalt prepared in Example 1.3 of the present application is significantly better than that of Comparative Examples 2-3. It can be seen that the present application uses butadiene-styrene microgel to modify the petroleum asphalt, which not only can obtain a modification effect that is better than that of polymers such as SBS rubber emulsion and butadiene-styrene latex, but also has good high-temperature storage stability, reducing the possibility of macroscopic phase separation of the polymer during storage due to insufficient temperature stability of the modified petroleum asphalt.
[0055] 4. In order to further compare the bonding performance of the petroleum asphalt modified with the styrene butadiene microgel of the present application with the petroleum asphalt modified with polymers such as SBS and styrene butadiene latex, the present application further refers to the method in DB61-T 1509-2021 "Technical Specifications for Interlayer Bonding Construction of Highway Asphalt Pavement" and uses the S / N ATD17908 bonding strength puller of DeFeIsko Company of the United States to test the room temperature pull-out strength of the modified petroleum asphalt prepared in Example 1.3 and Comparative Example 2-3 on the basalt substrate. The results are shown in Table 7.
[0056] Table 7 Adhesion performance results Unit: MPa project Pull-out strength Example 1.3 3.25±0.31 Comparative Example 2 1.28±0.17 Comparative Example 3 1.36±0.09 It can be seen from Table 7 that the room temperature pull-out strength of Example 1.3 on the basalt substrate is higher than that of Comparative Examples 2-3. It can be seen that the modified petroleum asphalt of the present application has a high adhesion to the interface, which further improves the stability and durability of the modified asphalt pavement, enhances the bearing capacity of the pavement, reduces pavement damage and maintenance costs, and improves driving safety.
[0057] 5. To further demonstrate the compatibility of the styrene butadiene microgel of the present application with petroleum asphalt, the present application further uses an acrylic microgel to replace the styrene butadiene microgel in step S2 of Example 1.3. The rest of the preparation method is the same as that of Example 1.3, and basic performance tests are performed on it. Through testing, it is found that the softening point and other properties of the petroleum asphalt modified by the acrylic microgel are not improved compared with those before modification. It can be seen that the styrene butadiene microgel of the present application matches the structure of petroleum asphalt and can have a good modification effect on petroleum asphalt, while other microgels that cannot match the structure of petroleum asphalt cannot achieve the modification effect of the styrene butadiene microgel.
[0058] The specific preparation method of the above-mentioned acrylic ester microgel is as follows: In 8 kg of water, a monomer mixture consisting of 8 kg of butyl acrylate (BA, analytical reagent), 0.3 kg of methacrylic acid (MAA, analytical reagent), 1 kg of styrene (St, analytical reagent) and 0.3 kg of trimethylolpropane trimethacrylate (TMPTMA, crosslinking agent, analytical reagent) was first added, and then 0.14 kg of SR-10 (allyloxy isomeric alcohol ether sulfate ammonium salt, an anionic reactive emulsifier, Shanghai Deyude Trading Co., Ltd.), 0.06 kg of An emulsifier system consisting of AEO-5 (fatty alcohol polyoxyethylene ether, a nonionic surfactant, Hai'an Petrochemical Plant, Jiangsu Province) and 0.04 kg of sodium bicarbonate (NaHCO3, analytical grade) was stirred at room temperature to disperse the monomer in water to form an emulsion, and then an initiator system consisting of 0.04 kg of potassium persulfate (K2S2O8, analytical grade) and 2 kg of water was added, and the reaction was carried out at 50°C for 6 hours under nitrogen protection to obtain an acrylic ester microgel emulsion with a solid content of 48 wt% and an average particle size of 0.137 μm (measured by a basic optical particle size analyzer).
[0059] In summary, the present application adopts a slightly cross-linked butadiene styrene microgel modified petroleum asphalt that is compatible with the structure of petroleum asphalt, which not only has higher performance than polymer-modified petroleum asphalt such as SBS rubber emulsion and butadiene styrene latex, but also can be stably stored at high temperatures, reducing the possibility of polymer macrophase separation during storage due to insufficient temperature stability of the modified petroleum asphalt, and improving the stability of the modified petroleum asphalt at viscous flow temperature. And when the addition amount or modification effect is equivalent, compared with polymer-modified petroleum asphalt, the butadiene styrene microgel modified petroleum asphalt of the present application has a lower viscosity, reduces the degree of aging caused by the need for a higher melting temperature of the modified petroleum asphalt during use, and extends the service life of the modified petroleum asphalt. In addition, the butadiene styrene microgel of the present application can also increase the interfacial adhesion between the modified petroleum asphalt and new and old aggregates, and improve the performance of the modified asphalt.
[0060] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A microgel modified asphalt, characterized in that: The invention comprises styrene butadiene microgel and asphalt, wherein the amount of the styrene butadiene microgel is 4-6wt% of the amount of the asphalt.
2. The microgel modified asphalt according to claim 1, characterized in that: The amount of the styrene-butadiene microgel used is 5wt% of the amount of asphalt used.
3. The microgel modified asphalt according to claim 1, characterized in that: The styrene butadiene microgel is prepared by cross-linking styrene butadiene latex by gamma irradiation, and the average molecular weight between the cross-linking points is 2500-22500 g / mol.
4. The microgel modified asphalt according to claim 3, characterized in that: The average molecular weight between the cross-linking points of the styrene-butadiene microgel is 10000-17000 g / mol.
5. The microgel modified asphalt according to claim 4, characterized in that: The average molecular weight between the crosslinking points of the styrene-butadiene microgel is 15000 g / mol.
6. The microgel modified asphalt according to claim 3, characterized in that: The polybutadiene content in the styrene-butadiene microgel is ≥10wt%.
7. The microgel modified asphalt according to claim 6, characterized in that: The polybutadiene content in the styrene-butadiene microgel is ≥50wt%.
8. A method for preparing microgel modified asphalt according to claim 1, characterized in that: The following steps are involved: S1, preparing styrene butadiene microgel, mixing styrene butadiene latex and a radiation sensitizer at room temperature, stirring evenly, and then sealing and standing and irradiating the mixture with gamma rays to obtain styrene butadiene microgel; S2, preparing microgel modified asphalt, mixing the styrene butadiene microgel prepared in step S1 and asphalt at a rotation speed of 800-1200 rpm for 5-8 minutes to obtain microgel modified asphalt.